A new short-time high-overload BLDC driving system based on electronic flywheel and time-division switching control. (August 2020) - Lu, Wenqi; Wu, Yaxiong; Zhu, Deming; Lu, Kaiyuan; Wang, Dong; Ye, Maosheng
Abstract: Most of the existing (BLDCM) brushless dc motor drive systems are designed with the traditional drive scheme for long-time operation. For short-time and heavy-duty applications, there are problems of energy consumption, large volume, heavyweight and high-cost. In this paper, a new short-time high-overload BLDCM drive system based on "electronic flywheel" and time-division switching control is proposed, which includes three core contents: a crushing chamber based on combined cutter head, an energy storage device based on an "electronic flywheel" and high overload factor BLDC using a new calculation method of capacitance and a speed control system based on time-division switching control of the speed loop and the current loop. To prove the effectiveness of the proposed scheme, a kitchen garbage processor is developed and tested. The results show that the "electronic flywheel" energy storage driving device designed in this paper is able to provide most of the energy required in the heavy-duty driving process. The designed time-division switching control scheme can well meet the control requirements for the short-time heavy load drive of the kitchen waste processor. Compared with the traditional long-time rated load drive scheme, the proposed system has the advantages of energy-saving, small volume, lightweight and low-cost.